Cover Image. Issue 6 (25th December 2021) - Sørensen, Line Bay; Rathleff, Michael Skovdal; Dean, Benjamin John Floyd; Oei, Edwin; Magnusson, Stig Peter; Olesen, Jens Lykkegaard; Holden, Sinéad
Abstract : The cover image is based on the Review Article A systematic review of imaging findings in patients with Osgood‐Schlatter disease by Line Bay Sørensen et al., https://doi.org/10.1002/tsm2.281 .